Device for placing people/cargo during evacuation thereof by helicopter - Honcharuk Hryhorii Mykolaiovych; Kuznetsov Oleksii Mykhailovych; Ponomarenko Valerii Ivanovych; Varakuta Serhii Vasyliovych (2010)
A device for placing people/cargo during evacuation thereof by a helicopter comprises a rack, five beams, a grid, ten cables, beam fasteners, upper fasteners of ropes and lower fasteners of ropes, a suspension unit, a fixing element of grid to the beams, a device for bringing of "beam-grid-cables" system in operating position, body belts with clasps and five basic attachments of body belts. The device also contains a fastener of safety belts, a pivot, wrist safety belts, a ring and a loop. Устройство для размещения людей/грузов при их эвакуации вертолетом содержит стойку, пять балок, сетку, десять тросов, узлы крепления балок, верхние узлы крепления тросов и нижние узлы крепления тросов, узел подвески, элемент крепления сетки к балкам, устройство приведения системы "балки-сетка-тросы" в рабочее положение, нательные ремни безопасности с карабинами и пять базовых узлов крепления нательных ремней безопасности. Устройство также содержит узел крепления ремней безопасности, пяту, наручные ремни безопасности, кольцо и петлю. Пристрій для розміщення людей/вантажів при їх евакуації вертольотом містить стійку, п'ять балок, сітку, десять тросів, вузли кріплення балок, верхні вузли кріплення тросів та нижні вузли кріплення тросів, вузол підвіски, елемент кріплення сітки до балок, пристрій приведення системи "балки-сітка-троси" у робоче положення, натільні ремені безпеки з карабінами та п'ять базових вузлів кріплення натільних ременів безпеки. Пристрій також містить вузол кріплення ременів безпеки, п'яту, наручні ремені безпеки, кільце і петлю.